THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE AT UPTD PUSKESMAS PINRANG - Yulistiana; Amiruddin Tawe; Muh. Ikhwan Maulana Haeruddin; Agung Widhi Kurniawan; Muh. Ilham Wardhana Haeruddin (Transpublika Publisher, 2023)
Motivation plays a crucial role in influencing employee performance across various dimensions. When employees are motivated, they exhibit higher levels of engagement, productivity, and commitment towards their work. The objective of this study is to examine the impact of work motivation on employee performance at UPTD Puskesmas Pinrang, Wajo Regency. Quantitative data was collected through questionnaires distributed to a sample of 51 individuals, specifically tailored to address the research problem. The collected data was then subjected to analysis using the simple linear regression method, with data processing performed using SPSS software to validate the research hypotheses. The findings indicate that the motivation variable yields a significant level of 0.000, which is smaller than the threshold value of 0.05. Moreover, the coefficient value of 0.650 demonstrates a positive influence on the dependent variable.